Morphological Study of The Pancreas and Duodenum in Adult Guinea Pigs (Cavia porcellus) - AL-Saffar, F. J.; Nasif, Riyadh H. (The Iraqi Journal of Veterinary Medicine, 2020)
The present study aimed to investigate the morphological features of the pancreas and duodenum of the adult males and females guinea pigs. Eight animals of each sex were collected to conduct this project. The selected organs were photographed in situ and macro morphometric measurements were conducted on them. Gross findings revealed that the pancreas of guinea pig was of compact type, of two lobes (right and left) connected by large central part (body). The organ drains the pancreatic secretion toward the last part of the ascending duodenum via minor pancreatic duct with absence of major pancreatic duct. The duodenum of the guinea pig was very short and V-shaped. The beginning of the duodenum contains duodenal papilla in which found central orifice for the exit of bile secretions of the common bile duct. In conclusions, the present findings showed the presence of only one minor pancreatic duct and such result was significantly different than most rodents by having major pancreatic duct. The duodenum in the studied guinea pigs was characteristically very short and V-shaped differently to other animals that have U-shaped and long duodenum.